Sosialisasi 3 Dosa Pendidikan di SMP Karya Bakti Jatilawang - Puja Kusuma, Tyas Pratama; Setiyoko, Sigit; Mu'amar, Wisnu; Arbianto, Arif; Harimurti, Hamar; Wardhani, Nabilla Alya; Mega Nanda, Nadira Aurira; Syarifah, Nur; Setiawan, Ito (Universitas Pahlawan Tuanku Tambusai, 2024)
The world of Indonesian education is experiencing big challenges due to the three big sins in the world of education, namely bullying, sexual violence and intolerance. The large number of cases that occur have an impact on hampering good cognitive development in children, as well as causing trauma that can even last the child's lifetime. Another challenge is that many students do not understand the 3 sins of education, as happened at Karya Bakti Jatilawang Middle School. Based on interviews with students, many of them do not know what the 3 sins of education are, the importance of knowledge about this matter is necessary, so it is necessary to provide information on the 3 sins of education and how to deal with them. The goal is for students to gain an understanding of what is prohibited, especially in the educational environment. The three major educational sins include bullying, sexual violence and intolerance. The training stages are the preparation stage, implementation stage and evaluation stage. The result of the training is an increase in students' understanding of what the 3 major sins are and how to deal with them.